"Hot-pressing welded" composite membrane for separating oil-in-water emulsion with high structural stability. (1st December 2020) - Huang, Dan; Zhang, Jie; Wu, Gang; Chen, Si-Chong; Wang, Yu-Zhong
Abstract: Electrospun nanofiber membrane has been focused on the application of separation materials for oily sewage attributing the success to its unique advantages, including large porosity, high specific surface area and complex open channel structure. However, its inherent high flexibility and easy deformability are not conducive to the stable separation performance of materials. Herein, we have developed a facile "hot-pressing welding" strategy to prepare nanofibrous composite membrane with high structural stability, which exhibit excellent comprehensive separation performance in a wide pressure range. The maximum fluxes for emulsions with/without surfactant reach up to 2340 and 7500 L m −2 h −1, respectively, with separation efficiency higher than 99%. In combination of the strong supporting ability of MF layer and stable porous structure of NF layer, the PDA@PLA-CF can separate the surfactant-stabilized emulsion efficiently under very wide range of vacuum degree from only gravity to relatively high negative pressure of 50 kPa without obvious decrease in separation efficiency, indicating its good adaptability to complex environment. Graphical abstract: Image 1 Highlights: A simple "hot-pressing welding" strategy to prepare composite membrane. Improving stability of porous texture of electrospun membrane. Stable separation performance within a wide range of external pressure.